PRODUCTION OF ALUMINIUM SULPHATE AND UTILIZATION OF CLAY RESIDUE FROM KAOLINITE CLAY - Akif, Muhammad; Zubair, Muhammad (Biological Sciences - PJSIR, 2004)
Preparation of aluminium sulphate from Kaolinite clay has been studied by calcinations with sodium chloride followed by sulphuric acid extraction. The calcination was carried out at 850 - 900°C for 3 h. The maximum recovery of alumina extracted as aluminium sulphate has been determined both on laboratory and pilot plant scale. The utilization of clay residue as an active puzzolanic material is discussed in this investigation.